Distribution and antimicrobial resistance profiles of bacterial species in stray cats, hospital-admitted cats, and veterinary staff in South Korea - Jung, Woo Kyung (BMC Vet Res, 2020)
BACKGROUND: Antimicrobial resistance is becoming increasingly important in both human and veterinary medicine. According to the One Health concept, an important step is to monitor the resistance patterns of pathogenic bacteria. In this study, the antimicrobial susceptibility patterns and trends of bacteria isolated from stray cats, hospital-admitted cats, and veterinary staff in South Korea between 2017 and 2018 were investigated. RESULTS: The minimum inhibitory concentrations of different antibiotics for Staphylococcus spp., Enterobacteriaceae, and Enterococcus spp. were determined to establish representatives of different antibiotic classes relevant for treatment or surveillance. For Coagulase-positive and Coagulase-negative Staphylococci, resistance to fluoroquinolones was below 13%, but resistance to ampicillin and penicillin was high (20–88%). A total of 9.5, 12.1, and 40.3% of staphylococcal isolates from stray cats, hospital-admitted cats, and veterinary staff, respectively, were confirmed to be mecA positive. For Enterobacteriaceae, resistance to carbapenems, fluoroquinolones, and 3rd generation cephalosporins was low (0–11.1%). The Enterococcus spp. isolates showed no resistance to vancomycin. The antimicrobial resistance rates of the Staphylococcus spp. and Enterobacteriaceae isolates from stray cats were usually lower than those of isolates from hospital-admitted cats and veterinary staff, but the Enterococcus spp. isolates revealed the opposite. Thus, the antimicrobial resistance varied across bacterial species according to the source from which they were isolated. CONCLUSIONS: Resistance to critically important compounds were low. However, the presence of antimicrobial resistance in cat isolates is of both public health and animal health concern.